2017
DOI: 10.1002/ajmg.a.38256
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic expression of 19q13.32 microdeletions: Report of a new patient and review of the literature

Abstract: The phenotypic manifestations of microdeletions in the 19q13.32 region are still poorly known. In this paper we report a patient who presented with hypotonia, developmental delay, facial dysmorphism, micrognathia, kyphoscoliosis, and buried penis. Chromosomal microarray revealed an interstitial 327 kb de novo microdeletion in the 19q13.32 region comprising eight genes (ARGHAP35, NPAS1, TMEM160, ZC3H4, SAE1, BBC3, MIR3190, and MIR3191). Previously reported cases of microdeletions in the 19q13.32 region were rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The authors concluded that the above-mentioned features are common features of 19q13.32 microdeletion syndrome, and that these features result from the deletion of 20–23 genes located in this region, among which are NPAS1, NAPA, ARGHGAP35, DHX34, SLC8A2, ZNF541, and MEIS3, genes that are expressed in the brain parenchyma, glial cells, musculoskeletal system, heart, and gastrointestinal system [ 14 ]. In 2017, Travan et al [ 24 ] described a fifth patient with a 327 kb deletion in this region, consisting of eight genes: ARGHAP35, NPAS1, TMEM160, ZC3H4, SAE1, BBC3, MIR3190, and MIR3191. The patient had hypotonia, facial dysmorphism, micrognathia, developmental delay, kyphoscoliosis, and a buried penis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors concluded that the above-mentioned features are common features of 19q13.32 microdeletion syndrome, and that these features result from the deletion of 20–23 genes located in this region, among which are NPAS1, NAPA, ARGHGAP35, DHX34, SLC8A2, ZNF541, and MEIS3, genes that are expressed in the brain parenchyma, glial cells, musculoskeletal system, heart, and gastrointestinal system [ 14 ]. In 2017, Travan et al [ 24 ] described a fifth patient with a 327 kb deletion in this region, consisting of eight genes: ARGHAP35, NPAS1, TMEM160, ZC3H4, SAE1, BBC3, MIR3190, and MIR3191. The patient had hypotonia, facial dysmorphism, micrognathia, developmental delay, kyphoscoliosis, and a buried penis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Travan et al [ 24 ] described a fifth patient with a 327 kb deletion in this region, consisting of eight genes: ARGHAP35, NPAS1, TMEM160, ZC3H4, SAE1, BBC3, MIR3190, and MIR3191. The patient had hypotonia, facial dysmorphism, micrognathia, developmental delay, kyphoscoliosis, and a buried penis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations